The Dissociative Symptoms Scale (DSS): psychometric properties of scores on a German version in clinical samples - Heekerens, Johannes; Biermann, Miriam; Mocarz-Kleindienst, Maria; Vonderlin, Ruben; Lyssenko, Lisa; Hofmann, Valerie X. C.; Carlson, Eve B.; Enning, Frank; Schmahl, Christian; Kleindienst, Nikolaus (Psychological assessment, 2025)
Dissociation is a widespread phenomenon with significant mental health implications. The 20-item Dissociative Symptoms Scale (Carlson et al., 2018) was developed to measure moderately severe levels of dissociation across a broad range of clinical populations. The factor structure of the Dissociative Symptoms Scale comprises four domains: Depersonalization/Derealization, Gaps in Awareness and Memory, Cognitive-Behavioral Reexperiencing, and Sensory Misperceptions. In this article, we present a German version of the Dissociative Symptoms Scale (G-DSS) and examine the psychometric properties of scores on the G-DSS. Across two studies (Ntotal = 257) involving clinical samples primarily composed of individuals with depressive disorders, borderline personality disorder, and posttraumatic stress disorder, we demonstrate that G-DSS scores mostly align with the expected four-factor structure. In addition, G-DSS scores demonstrated adequate internal consistency (ω ≥ .76 for subscales), strong convergent validity with large correlations to scores on other dissociation measures, good discriminant validity with small or nonsignificant correlations to scores on personality facets, and good concurrent validity with positive correlations to scores on psychopathology indicators. We conclude that scores on the G-DSS are reliable and valid for assessing dissociative symptoms in clinical populations similar to the samples studied, which can enhance our understanding of dissociation’s structure and clinical implications. (PsycInfo Database Record (c) 2025 APA, all rights reserved)
Gesehen am 24.11.2025